Civic and university ethics: more than an obvious relationship Some guidelines for the practical teaching of university professors, University of Costa Rica, 2022 - Cambronero Alpízar, José Rodolfo (2023)
Living in society implies the determination of shared values ​​that guide and inspire common life. Ethics training in universities responds to this human aspiration that, although theoretically necessary, entails multiple knots to clear. This article aims to identify the roots and opportunities of ethics training in the context of university teaching practices at the University of Costa Rica. The approach to this phenomenon is based on the analysis of university experiences both in its normative aspect and in the opportunities that arise in teaching practices in the context of ethics training. The relationships established in the article make it possible to determine the relevance of some teaching practices in the formation of ethics, understood as a social construction of values ​​by individuals capable of deciding what is good for their particular and social contexts.